TelereHUB-CHILD: An online integrated knowledge translation tool to optimize telerehabilitation evidence-based practices for children with disabilities and their families - Ogourtsova, Tatiana (Frontiers in Rehabilitation Sciences, 2023)
Background Pediatric telerehabilitation has been quickly adopted by clinicians during the pandemic. This precipitated shift in the model of healthcare delivery is significant and compounded by clinicians' training and knowledge needs related to evidence-based practices. This instigated a knowledge translation initiative TelereHUB-CHILD—an online platform designed for clinicians, patients, and families. The aim of this brief report is to describe its development, including the roles of key stakeholders in these processes. Methods Following a systematic review on telerehabilitation, a series of co-creation activities with clinical (n = 24 rehabilitation professionals) and parent-partners (n = 4 parents of children with disabilities) were undertaken. Clinical partners were engaged in five web-activities. These were designed to gather their feedback regarding training and knowledge needs, present preliminary findings of the systematic review and explore their perceived importance and usefulness with respect to different sections of TelereHUB-CHILD, including Tele-treatments, Tele-Assessments, and Resources. Parent-partners were engaged asynchronously to provide feedback on the content and presentation of the Patient/Family Information section. Results Clinical partners reported moderate-high usefulness and importance with each section of the tool and the presented features. As per partners' feedback, the Tele-treatments section provides standardized summaries outlining the effectiveness of the tele-treatment approach and the level of the evidence for each outcome of interest, according to the different diagnosis groups and professional discipline. For patients/family, common questions and answers can be explored in three user-friendly formats, including printable learning briefs, onsite accordions, and animation videos. The Tele-assessments section outlines existing measures by professional discipline. Resources offer preparatory forms for families and clinicians, questionnaires, and other learning material. Conclusion TelereHUB-CHILD was co-developed with key stakeholders. It can guide telerehabilitation evidence-based practices, empower patients and families, and pinpoint research and practice gaps.